PRO: Redistricting of United Network for Organ Sharing Regions to Improve Geographic Disparities in Liver Transplantation. Issue 2 (7th September 2018) - Calmet, Fernando H.; Samuel, Maria; Martin, Paul
Abstract : Watch a video presentation of this article Watch the interview with the author